2022
DOI: 10.1186/s12913-022-07711-1
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to tuberculosis case finding in primary and secondary health facilities in Ghana: perceptions, experiences and practices of healthcare workers

Abstract: Background Ghana’s national tuberculosis (TB) prevalence survey conducted in 2013 showed higher than expected TB prevalence indicating that many people with TB were not being identified and treated. Responding to this, we assessed barriers to TB case finding from the perspective, experiences and practices of healthcare workers (HCWs) in rural and urban health facilities in the Volta region, Ghana. Methods We conducted structured clinic observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 40 publications
0
9
1
Order By: Relevance
“…The lack of TB training could partly explain why over 30% of our participants attributed their non-referral to not having seen a presumptive TB case yet, which is reflected by the high number of respondents who could not give the right case definition. Although staff turnover was highlighted as creating a knowledge gap in TB case detection in a study on barriers to TB case finding in Ghana [24], this did not come up as a barrier to referral in our study. Of the respondents, 10.5% and 26.3% in the pre-defined and free text responses respectively attributed non-referral to a lack of financial support by the TB programme leading to some operators reporting to have to bear the cost of transportation for the customers they referred.…”
Section: Discussioncontrasting
confidence: 64%
“…The lack of TB training could partly explain why over 30% of our participants attributed their non-referral to not having seen a presumptive TB case yet, which is reflected by the high number of respondents who could not give the right case definition. Although staff turnover was highlighted as creating a knowledge gap in TB case detection in a study on barriers to TB case finding in Ghana [24], this did not come up as a barrier to referral in our study. Of the respondents, 10.5% and 26.3% in the pre-defined and free text responses respectively attributed non-referral to a lack of financial support by the TB programme leading to some operators reporting to have to bear the cost of transportation for the customers they referred.…”
Section: Discussioncontrasting
confidence: 64%
“…Limited infrastructure is not unique to PNG; other studies in South Africa, Pakistan, China, and Bangladesh found that inadequate isolation and ventilation facilities in healthcare facilities have limited the operationalization of recommended TB-IPC measures(35, 36). Another similar situation was observed in Ghana, where similar shortcomings increased TB transmission(37). A continuing lack of essential health infrastructure, such as a TB ward in district hospitals, will signi cantly impact TB-IPC strategies and, in turn, the development and transmission of TB among patients, HCWs, and communities.…”
mentioning
confidence: 58%
“…Lack of community awareness about tuberculosis was reported as one of the factors related to delays in care seeking for tuberculosis and diagnosis in a study conducted in Indonesia [34]. Many HCWs further reported that stigma associated with tuberculosis and fear of COVID-19 may have prevented parents from accurately reporting on symptoms among their children at screening, as was shown recently in Ghana [35]. Transport, distance, and electricity supply were repeatedly mentioned as barriers to the acceptability of decentralization, hampering referral of patients – including for chest X-Ray, samples and test results between PHCs and DHs, in both directions.…”
Section: Discussionmentioning
confidence: 99%